Tuberculosis Treatment Failure: Causes and Solutions - (:unkn) unknown (NOVA SCIENCE PUBLISHERS, INC, 2010)
The article attempts to examine the main reasons why the treatment of tuberculosis is not always successful, and to propose possible solutions to address this failure. In the introductory section a brief review of tuberculosis epidemiology includes encouraging global progress over the past twenty years tempered by some ongoing areas of concern. The main reasons for treatment failure are thought to be drug resistance and non-adherence to therapy. The first major reason for treatment failure is resistance to anti-tuberculosis agents. The underlying causes of this drug resistance and the types of drug resistance that a practitioner may encounter, is briefly explained. One of the areas of concern mentioned above is the relatively high levels of multiple-drug resistance tuberculosis (MDR-TB) in Eastern Europe, former Soviet countries and in densely populated Asian countries. To this should be added the disturbing emergence of extensive drug resistance (XDR-TB). Successful treatment approaches in managing drug resistance and barriers to effective treatment outcomes are also concisely dealt with. The second foremost cause of treatment failure is non-adherence. In the opening section dealing with this topic, the terms adherence and non-adherence are defined; this is followed by a succinct section on how adherence can be evaluated and factors which can affect adherence, either positively or negatively. A slightly more expanded section deals with the important topic of how adherence to TB treatment can be improved by focusing on patient-centered strategies. Following this, the benefits of directly observed therapy (DOT) as a way of ensuring adherence is discussed, and an overview of the success of DOT programs is provided, both in terms of patients with drug sensitive and drug resistant tuberculosis. The pharmaco-economic implications of DOT strategies are also alluded to in a few words. In the final section, a number of possible solutions to prevent and overcome the problem of treatment failure is brought together is the form of a list of proposals. Most of these proposed solutions are already mentioned in the main body of the text.
Keywords: MULTIDRUG-RESISTANT TUBERCULOSIS; DIRECTLY OBSERVED THERAPY; MYCOBACTERIUM-TUBERCULOSIS; PATIENT EDUCATION; DRUG-RESISTANCE; PYRAZINAMIDE; PREVENTION; RIFAMPICIN; ADHERENCE; REGIMENS